Development and implementation of the physiotherapy-led exercise interventions for the treatment of rotator cuff disorders for the 'Getting it Right: Addressing Shoulder Pain' (GRASP) trial. (June 2020) - Keene, David J; Soutakbar, Hessam; Hopewell, Sally; Heine, Peter; Jaggi, Anju; Littlewood, Chris; Hansen, Zara; Barker, Karen; Hamilton, Willie; Carr, Andrew J.; Lamb, Sarah E.
Abstract: Objectives: The Getting it Right: Addressing Shoulder Pain (GRASP) trial is a large-scale, multicentre, 2 × 2 factorial randomised controlled trial investigating clinical and cost-effectiveness of a progressive exercise programme versus best-practice advice, with or without corticosteroid injection, for treating people with rotator cuff disorders. Here we describe the development, implementation and details of the physiotherapy-led interventions. Methods: Medical Research Council guidance for developing complex interventions were used, taking into account clinical guidelines, expert and patient opinion, research evidence, current practice variation, and deliverability. A stakeholder meeting of 26 experts, clinicians, researchers, and patient representatives was used to design key components of the interventions. Stakeholders prioritised strengthening posterior rotator cuff muscles and using practical, easy-to-do exercises. The interventions were designed to be deliverable across the UK National Health Service. Results: Progressive exercise consists of up to six sessions with a physiotherapist over 16 weeks. The best-practice advice consists of one face-to-face session with a physiotherapist with substantially greater reliance on self-management. Both interventions include self-management advice, home-exercise instruction, and behaviour-change strategies to target exercise adherence. All participants receive a Participant Information Booklet. The best-practice advice intervention is a self-guided system of progressively challenging exercises, with demonstration videos and written materials. The progressive exercise intervention has a wider range of exercise options, and greater flexibility for tailoring, progression, supervised practice and feedback. Conclusion: GRASP has recruited 708 participants and will provide high quality evidence to inform management of people with shoulder pain due to a rotator cuff disorder. Results are anticipated in 2020. Trial registration number: ISRCTN16539266; EudraCT number:2016-002991-28.